Pengaruh Cost Of Quality Terhadap Tingkat Design Quality Produk - Budi Lesmana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
Quality has become part of the business strategy to increase competitive advantage. Companies that use quality as a strategic tool will have a competitive advantage over their competitors in controlling the market. This research aims to determine and obtain data on Total Quality Management used in regulating the cost of quality and the level of design quality, so as to explain the relationship and influence between the components of quality costs and the level of design quality, also to determine the effect of the influence of cost of quality, cost prevention, appraisal cost, internal failure cost, external failure cost, to the level of design quality, thus it is expected to provide benefits to all parties who are interested in and have an interest in product quality issues, both for companies and the general public as users of the products produced. The research method used is descriptive-analytical method with a case study approach and the research analysis was carried out by quantitative testing with the help of the Path Analysis Method so that the research results obtained that the Cost of Quality greatly influences the results of design quality either partially or simultaneously. The influence of the effect of cost of quality simultaneously on design quality is 89.3647%, the remaining 10.6353% is the influence of other influences not examined and the closeness of the relationship between prevention cost and appraisal cost is 0.35884, between prevention cost and internal failure cost is -0.50510 , between prevention cost and external failure cost is -0.29592, between prevention cost and design quality is -0.67462 so that companies are expected to pay more attention in the future and increase the components of prevention cost and appraisal cost which will reduce internal components. failure cost and external failure cost so that product quality will be maintained.